Cognitive behavior therapy for menopausal symptoms (CBT-Meno): a randomized controlled trial. Issue 9 (September 2019) - Green, Sheryl M.; Donegan, Eleanor; Frey, Benicio N.; Fedorkow, Donna M.; Key, Brenda L.; Streiner, David L.; McCabe, Randi E.
Abstract: Objective: To evaluate the effectiveness of cognitive behavioral therapy for menopausal symptoms (CBT-Meno) compared with a waitlist condition (no active intervention). A randomized controlled trial was conducted with 71 perimenopausal or postmenopausal women who were seeking treatment for menopausal symptoms. Methods: Blind assessments were conducted at baseline, 12 weeks postbaseline, and 3 months post-treatment. An intention-to-treat analysis was conducted. CBT-Meno sessions included psychoeducation, and cognitive and behavioral strategies for vasomotor and depressive symptoms, anxiety, sleep difficulties, and sexual concerns. Primary outcomes were scores on the Hot Flash Related Daily Interference Scale (HFRDIS) and Beck Depression Inventory (BDI-II). Secondary outcomes were scores assessing vasomotor and sexual concerns on the Greene Climacteric Scale (GCS-vm, GCS-sex), the Montgomery-Åsberg Depression Rating Scale (MADRS), Hamilton Anxiety Rating Scale (HAM-A), Pittsburgh Sleep Quality Index (PSQI), and the Female Sexual Function Index (FSFI). Results: There were significantly greater improvements in CBT-Meno compared with waitlist in vasomotor symptom interference (HFRDIS; P < 0.001, η 2 P = 0.21) and "bothersomeness" (GCS-vm; P = 0.04, η 2 P = 0.06), depressive symptoms (BDI-II; P = 0.001, η 2 P = 0.15), sleep difficulties (PSQI; P = 0.001, η 2 P = 0.17), and sexual concerns (GCS-sex; P = 0.03, η 2 P = 0.07). These results were found even when controlling for menopausal staging and medication use. Gains were maintained at 3 months post-treatment. Conclusions: CBT-Meno was particularly effective in improving self-reported vasomotor symptoms, depressive symptoms, sleep difficulties, and sexual concerns. Although future studies will be needed to confirm the impact of CBT-Meno on anxiety symptoms, these results suggest that this protocol is effective in targeting commonly reported menopausal symptoms. N/A: Video Summary: Supplemental Digiatl Content 1, http://links.lww.com/MENO/A416 Abstract : Supplemental Digital Content is available in the text